PENGARUH CITA RASA, SLOGAN, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN - Prastyo, Nanda Ade; Pujianto, Agung; Nasution, Ute Ch (Jurnal Dinamika Administrasi Bisnis, 2018)
The city Surabaya especially now growing very rapidly culinary business that offers a variety cooking, will of Indonesia and abroad. Stall rawon calculator one culinary business in Surabaya different and unique of culinary business another. Culinary business has been standing 36 years and currently survive. Research is called influence flavor, slogans and quality of service for customer satisfaction (case studies on a stall rawon calculator Surabaya).This study attempts to explain the influence of flavor, slogans, and the quality of service to customer satisfaction in a stall rawon calculator. Research instruments used is a questionnaire to be distributed to 100 customer. Rawon calculator. Next, the data that has been collected using analysis of multiple regression mixed with aid application IBM SPSS 22. The quality of services most dominant their influence on customer satisfaction stall rawon calculator. The result showed that the influence of flavor of customer satisfaction, flavored and slogans simultaneously influential positive and significant. While the quality of services have a dominant influence of customer satisfaction.Keywords: flavor, slogan, the quality of service, customer satisfaction